FRET in Orthogonal, Increasingly Strain‐Rigidified Systems. Issue 5 (8th August 2021) - Langhals, Heinz; Dietl, Christian; Mayer, Peter
Abstract: The influence of the geometry factor κ on the efficiency of energy transfer by FRET (Förster resonance energy transfer) was studied by means of dyads of benzoperylene and perylene interlinked by a spacer of the cage bicyclo‐[2.2.2]octane. The electronic transition moments were arranged orthogonally for extinguishing the energy transfer according to Förster's theory. In contrast to the theory energy transfer proceeded unrestrictedly attributed to molecular vibrations. A further rigidifying of the spacer by means of annellation with benzo groups until the very rigid triptycene as a spacer could not hinder the energy transfer so that general strongly coupled molecular framework vibrations seem to be dominant in the energy transfer whereas molecular flexibility seems to be of minor importance. Application such as molecular mirrors are discussed. Abstract :